Behind the Canvas: A Novel Exploring Childhood Verbal Abuse’s Effects on Adolescents’ Behavioral Development - Olivia Agatha; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
The number of child abuse, particularly verbal abuse, has been increasing over the past decades. The increase happens because of some people’s rationalization toward verbal abuse, especially because they believe that verbal abuse is an effective discipline method for their children. Reflecting on this reality, this creative work highlights the issues of childhood verbal abuse on the victims’ behavioral development by displaying the types, the consequences, and the healing steps of childhood verbal abuse. The exploration of the aforementioned issues is supported by Rohner’s Parental Acceptance-Rejection Theory and Bowlby’s Attachment Theory. The form of this creative work is a bildungsroman novel about the journey of a boy named Elliot who suffers from verbal abuse from his mother due to his birth origin.